The principle of judicial non interference in arbitrations: Comments on Article 3 of the Peruvian Arbitration Law - Velásquez Meléndez, Raffo (2021)
The virtues of arbitration depend on the principle of judicial non-interference in its proceedings and on a limited regime of subsequent judicial control of arbitrations. However, there is a lot of confusion about the articulation of the different procedural control channels applicable to arbitrations, the timing of their activation and their scope. Article 3 of the Arbitration Act establishes the principle of judicial non-interference, but it needs to be understood within the entire framework of existing procedural defenses. For these purposes, the history of national and comparative jurisprudence plays an extremely relevant role.